PEMIKIRAN ISLAM DALAM PERSPEKTIF SUNNI DAN SYI’AH - Itmam, Muh. Shohibul (Jurnal Penelitian, 2013)
THE ISLAMIC THINKING IN SUNNI AND SYI’AH PERSPECTIVES. This paper attempts to describe the problems associated with Islam in particular with regard to Sunni and Syi’ah teachings. The number of  streams that developed in Islam today has resulted Islam got claims from various clerical community, such as terrorism and others, resulting in the ruination image of  Islam in the constellation of  the religions of  man. As the flow and the teachings of  the most dominating civilization of  the world religions, Sunni and Syiah, including the Wahhabi, are necessary to clarify the existence or clarified the diversity in the constellation of  Islam, considering the number of streams that are currently claiming truth on themselves. Iran as the country becoming a reference in the world of  developing Syi’ah should be used as a reference in the study of  understanding associated with Sunni and Syi’ah. From this country, the world of  Islam knows the concept ofgoverning “Wilayatul Faqih”. The concept was pioneered by the government of Imam Khomeini who became known after Islamic Revolution in Iran 1979 and continues to be developed up to now. Every year Iran is celebrated with a huge demonstration with the slogan in Persian, “Islam Pyruz ast, ast Nabud Istikbar”, Islam is victorious, crushed the vanity of the islam enemy.keywords: Islam, Sunni, Syi’ah, Perspective, Differences, Similarities.Tulisan ini mencoba mengurai persoalan yang berhubungan dengan Islam secara khusus yang berkaitan dengan ajaran Sunni dan Syi’ah. Banyaknya aliran yang berkembang dalam Islam dewasa ini telah mengakibatkan Islam mendapat klaim dari berbagai komunitas agamawan, seperti teroris dan lainnya, yang mengakibatkan redupnya citra Islam dalam percaturan agama-agama manusia. Sebagai aliran dan ajaran yang paling mendominasi peradaban agama dunia, Sunni dan  Syi’ah,  termasuk  Wahabi,  perlu  memperjelas  eksistensinya atau diperjelas keberagamaannya dalam percaturan agama Islam, mengingat banyaknya aliran yang dewasa ini mengklaim kebenaran atas dirinya. Iran sebagai negara yang menjadi rujukan dunia dalam mengembangkan ajaran Syi’ah patut dijadikan rujukan dalam studi pemahaman yang berhubungan dengan Sunni dan Syi’ah. Dari negara Iran, dunia Islam mengenal konsep pemerintahan “Wilayatul Faqih”. Konsep pemerintahan ini dipelopori oleh Imam Khumaini yang mulai dikenal setelah Revolusi Islam Iran pada tahun 1979 dan terus dikembangkan hingga sekarang. Setiap tahun di Iran diperingati dengan demonstrasi besar-besaran dengan semboyan dalam bahasa Persia, “Islam Pyruz ast, Istikbar Nabud ast”, Islam jaya, hancur kesombongan musuh Islam.kata kunci: Islam, Sunni, Syi’ah, Perspektif, Perbedaan, Persamaan.